ChemInform Abstract: Trifluoromethylation of 1‐Aryl‐3, 3‐diisopropyltriazenes. Issue 32 (18th July 2013) - Hafner, Andreas; Braese, Stefan
Abstract The new and facile two‐step, one‐pot synthesis affords various functionalized fluoroalkyl‐substituted arenes.